Incidencia de la actividad petrolera sobre el crecimiento económico de la región Loreto periodo 2017 – 2021 - Sanchez Mozombite, Tyffani Briggitte (2023)
The main objective of this thesis was to analyze the relationship between oil activity and economic growth in the Loreto region. To achieve this, the estimation method of the dynamic regression model was employed. Additionally, a confidence level of 95% was established to verify the significance of the obtained results. The research was based on the premise that oil activity can have a significant impact on the economic growth of a region. Relevant data on oil activity and economic growth in the Loreto region were collected during the period 2017-2021. Through the analysis of dynamic regression, the relationship between oil activity and economic growth was examined. The results revealed that a one-percentage-point increase in oil activity was associated with a 0.0512 percentage point increase in economic growth in the Loreto region. This finding was statistically significant at the 95% confidence level. In conclusion, this study provides empirical evidence supporting the idea that oil activity has a positive incidence on economic growth in the Loreto region. These results can be useful for decision-makers in the economic and energy fields as they offer a solid basis for considering policies and strategies that promote sustainable development in the region through oil activity.